Game-based learning for basic programming courses: Discover students’ attitudes and interests - Quah, Wei Boon; Mohd Banua, Noraini; Zulkifle, Zulhana (Journal of ICT in Education, 2025)
The basic programming course is one of the challenging, difficult, and complex courses for community college students at Kedah State. In this course, students must know the basic concepts and structures as well as the basic syntax of computer programming. The challenge is that students are less interested in learning theoretically and have difficulty creating programming code to solve simple programming problems. In this study, three objectives are pursued: (i) to determine students’ attitudes toward the basic programming course, (ii) to determine students’ interest in using the C# VENTURE application game, (iii) to determine differences in students’ attitudes toward the basic programming course according to gender, and (iii) to determine differences in students’ interest in the C# VENTURE application game according to gender. There were 54 participants in this study. In this study, questionnaires were used as instruments, which were distributed through Google Forms. The results show that the mean score of (4.18) for students’ attitudes is at a high level. In addition, students’ interest in C# VENTURE application games is also high with a mean of (4.47). The results of the independent samples t-test showed that there is no significant difference in the mean attitude of students for male and female student groups. The results of the t-test for independent samples also show that there is no significant difference between the average student interest in the C# application game VENTURE for male and female student groups. In conclusion, community college students are positive towards the basic programming course, although this course is very difficult and complex. Moreover, students showed a great interest in using C# VENTURE application games in teaching and learning (T&L) for this course. It is proposed to conduct a quasi-experimental study to investigate the effectiveness of the C# VENTURE application game in teaching and learning (T&L) for the basic programming course.